The Effect of Online Food Delivery Service Quality on Customer Satisfaction and Customer Loyalty: The Role of Personal Innovativeness - Patrick Alexander Wilhelm Smith; Pantri Heriyati (Business and Entrepreneurial Review, 2023)
The online food delivery mobile service industry has emerged as a new channel of food delivery and marketing to capture a bigger share and sale in the food industry. This modern sort of business conveyance has gotten to be exceptionally prevalent, particularly among youthful, active, and working individuals. In addition, this business has become more competitive due to the increasingly new business entries and users’ expectation resulted from the anxiety of online food ordering and time convenience, but not at the expense of providing quality products and services. Subsequently, it is exceptionally vital that online benefit suppliers get it the nature and necessities as well as the related angles of the online benefit industry that are considered critical to the clients in this developing market. This study tries to explore and gauge information to guide the online service providers regarding the requirements and attributes of this new service delivery system. Using adopted questionnaire from Mobile Service Quality (M-S-QUAL), this study aims to investigate the relationships between customers perceived service quality of online food delivery (OFD) and its influence on customer satisfaction and customer loyalty, moderated by personal innovativeness. The data are collected from the customers or users of any online food delivery service and will be analyzed using correlations and Hierarchical Moderated Regression Analysis.